Advances in the economic analysis of participatory and labor-managed firms. Vol. 11 - Eriksson, Tor (Advances in the economic analysis of participatory and labor-managed firms., 2010)
"This volume includes theoretical and empirical research into changing institutions and employee participation. Topics covered include: the experience with employee ownership in relation to the fast change of institutions in transitional countries including those in Eastern Europe, the former Soviet Union, and China; the influence of the specific institutional setting on development; e.g. for the Mondragon Group of coops or the Italian Cooperative Associations, development as affected both by the institutional structure within the group and the surrounding institutions; the influence of legislation in different countries of conditions for the development of different types of employee participation; the re-shaping of the role of the employees as company stakeholders and the impact of these changes on employee motivation, effort and productivity; the impact of new employee incentive schemes, reward structures or other incentive mechanisms (if any) on firm productivity and financial performance; evidence of the implementation and effects of the employee share-ownership education; the impact of different informal institutions (culture) on the development and performance of different forms of employee participation."